Strategic questions in food and beverage management - Wood, Roy C. 1959- (Hospitality essentials series, 2018)
This book provides students with a series of critical reviews of issues in food and beverage management addressing a variety of managerial dilemmas of a more complex nature such as how important is the meal experience and is food an art form? These are accompanied by discussion points, questions, and case studies to aid application, critical thinking and analysis.--Provided by publisher.